ANALISIS PENGGUNAAN INSTRUMEN TES BERBASIS RANKING TASK DAN URAIAN DALAM MENGUKUR PRESTASI BELAJAR FISIKA SISWA - Wiguna, Aditya Putra; Wijaya, Agus Fani Chandra; Setiawan, Andhy (WaPFi (Wahana Pendidikan Fisika), 2013)
Reffer to the background study on 25 students in one of senior high school in Cimahi and interview with one of physics teacher about test, show that 80% of students revealed usual form of matter that they get is multiple choice tests, whereas 20% of students revealed usual form of matter that they get is essay test. In this situation, 60% of the way students answer the test in collusion with their partner, 28% of the way students answer test with cheating to their partner, whereas remaining 12% of perfunctory answer. Implementation of the test purposes in this school to measure student’s learning physics achievement. The research goal is to compare the equality between descriptions test and ranking test as instrument test into measure student’s achievement of learning physics. Descriptive research worked as the research design with Single Group Design and equalization design used Single Group Design. Population of study is students at 10th grade of SMK Bandung, whereas the sample is 54 students at tenth grade. Determinate this sample used purposive sampling technique. In the implementation, descriptive test and ranking task to be formative test concurrently.  The result of the research to showed the second variance value test 0,06 lower than table variance value, in this case to showed ranking task equivalent to descriptive test in measuring students’ achievement of learning physics. Thereby ranking task can be used as instrument test to measure students’ achievement of learning physics.